2016
DOI: 10.1002/erv.2448
|View full text |Cite
|
Sign up to set email alerts
|

Internal Structure and Measurement Invariance of the Dutch Eating Behavior Questionnaire (DEBQ) in a (Nearly) Representative Dutch Community Sample

Abstract: The Dutch Eating Behavior Questionnaire is a widely used instrument for assessment of emotional, external and restrained eating. The aim of the present study is to (i) analyse its internal structure using exploratory structural equation modelling; (ii) to assess its measurement invariance with respect to sex, BMI, age and level of education; and (iii) to evaluate the relations of the factors with these variables. Except that women were slightly over-represented, the sample (n = 2173) closely followed the socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 23 publications
8
43
2
2
Order By: Relevance
“…Studies have shown that the level of emotional eating depend on age and level of education [42]. With better education and younger age, the tendency towards emotional eating increases [41]. It can therefore be concluded that differences between the results obtained in the current and other studies are due to socio-demographic differences between samples.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Studies have shown that the level of emotional eating depend on age and level of education [42]. With better education and younger age, the tendency towards emotional eating increases [41]. It can therefore be concluded that differences between the results obtained in the current and other studies are due to socio-demographic differences between samples.…”
Section: Discussioncontrasting
confidence: 58%
“…The results of the current study may be additionally explained in the context of age and education [41]. In females, the higher the degree of flexible restrictions on eating, the lower the body fat and waist circumference [18].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…research with different adult samples has reported adequate psychometric properties for the questionnaire, not just in its original version (van strien et al, 1986) but also in its adaptation to english (Wardle, 1987), French (lluch et al, 1996), turkish (Bozan et al, 2011), italian (Dakanalis et al, 2013), and spanish (cebolla et al, 2014). several studies support the adequate internal consistency of the questionnaire in adult samples (Barrada, van strien, & cebolla, 2013;Bozan et al, 2011;cebolla et al, 2014;Dakanalis et al, 2013;lluch et al, 1996;van strien et al, 1986;van strien & Koenders, 2012), as well as its three-factor internal structure measuring dietary restraint, emotional eating and external eating (Barrada et al, 2013;Bozan et al, 2011;cebolla et al, 2014;Dakanalis et al, 2013;lluch et al, 1996;van strien et al, 1986). a gender effect has also been found, with women scoring higher than men on the DeBQ (Dakanalis et al, 2013;pothos, tapper, & calitri, 2009;Wardle, 1987).…”
Section: Introductionmentioning
confidence: 81%
“…to eat when you have nothing to do?' (25,27); Item 28 'Do you have the desire to eat when you are bored or restless?' (25); and Item 21 'Can you resist eating delicious food?'…”
Section: Introductionmentioning
confidence: 99%